The Reconstruction after a Giant Phyllodes Tumor Resection Using a DIEP Flap - Tsuruta, Yuki (Plast Reconstr Surg Glob Open, 2020)
A phyllodes tumor of the breast is a rare neoplasm, accounting for 0.3%–1% of all breast cancers. The size is 4–5 cm on average but sometimes the tumor grows more and involves the entire breast. As for treatment, complete surgical resection is the standard for localized breast phyllodes tumors. The reconstruction of a large defect is challenging. Herein, we present a case where a deep inferior epigastric artery perforator (DIEP) flap was used in breast reconstruction for a 48-year-old woman who was suffering from a giant phyllodes tumor. Immediate reconstruction was performed after tumor excision; the specimen weighed 4,230 g and the skin defect was 22 × 24 cm. The deep inferior epigastric artery and vein were anastomosed to the right internal mammary artery and vein, and the superficial inferior epigastric vein was anastomosed to the right lateral thoracic vein. The postoperative course was uneventful and the DIEP flap survived completely. In the setting of the reconstruction for a large defect, we must make maximum use of the limited human tissue available and ensure minimum damage, while also considering the functional and aesthetic outcome of the donor site. Various ideas and technologies have been reported that can assist in achieving this goal, but few reports have commented especially on the reconstruction of giant phyllodes tumor using autologous tissues. There were some other options for the way of the reconstruction such as a latissimus dorsi flap and a rectus abdominis flap. Compared with these approaches, using a DIEP flap has some disadvantages such as the need for the microsurgical skill and the risk of postoperative hernia. However, a DIEP flap provides the enough tissue to cover the large defect without any damage of the muscle. To our knowledge, this case was the largest phyllodes tumor reconstruction ever, in terms of the amount of the skin needed and resected tissue involved. Although more studies and longer follow-up will be required in the future, this case may show the usefulness of DIEP flaps for reconstruction of a giant phyllodes tumor.